Relationship Model of Compensation, Motivation, Job Satisfaction and Employee Performance - Ariani, Dorothea Wahyu (International Review of Management and Marketing, 2023)
Employee performance (EP) is an important variable that can improve company performance. Many studies have examined various factors that influence EP. Compensation, motivation, and job satisfaction (JS) are three important variables that have been shown to have an effect EP. This study aimed to examine the model of the relationship between the four variables. By using 520 government company employees in Yogyakarta, Indonesia, the results of model testing proved that compensation, motivation, and JS were related to EP. The results of the mediation model testing using structural equation modeling (SEM) found that motivation also played a role as a mediating variable for the relationship between financial rewards and EP. In this relationship model, motivation was able to increase JS, but employees who feel satisfied cannot guarantee that they will perform better.